Investigation on the behavior of three dimensional steel building due to lateral loading using csc software - Loi,, Hie Ping. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This research is aimed to investigate the behavior of three dimensional steel building due to lateral loading. Th ere are four models being developed to achieve the objectives of this study. The main objective of this study is to determine the sway or non sway criteria of the three dimensional seven storey model by using S-FRAME and S-STEEL software under Computer Services Consultants (CSC) UK Limited. S-FRAME is used to analyses the structure of building while S-STEEL is used to design the structure of the building. From the study, the result shows that the crite ria of sway and non sway are depend on the elastic critical load factor, λ cr, of the frame. Due to notional horizontal force and vertical force applyed on the three dimensional braced frame structure, the deflected shape of the structure is very small. The lowest λ cr value of the brace frame structure with pin connection is 6.3623 while the λ cr value for the brace frame with fixed connection is 16. 975 which is 63 % more than the brace frame with pin connection. From that, it can be concluded that, the three dimensional seven storey brace frame structure with pin connection is classified as sway frame, while the three dimensional seven storey brace frame with fixed connection is classified as non sway fr ame. It again proves that S-FRAME and S-STEEL is a powerful design tools. User-friendly manual procedures are constructed as written in the Chapter 4.